Interface Capture Effect Printing Atomic‐Thick 2D Semiconductor Thin Films. Issue 49 (26th October 2022) - Li, Lihong; Yu, Xiaoxia; Lin, Zhaoyang; Cai, Zhenren; Cao, Yawei; Kong, Wei; Xiang, Zhongyuan; Gu, Zhengkun; Xing, Xianran; Duan, Xiangfeng; Song, Yanlin
Abstract: 2D semiconductor crystals offer the opportunity to further extend Moore's law to the atomic scale. For practical and low‐cost electronic applications, directly printing devices on substrates is advantageous compared to conventional microfabrication techniques that utilize expensive photolithography, etching, and vacuum‐metallization processes. However, the currently printed 2D transistors are plagued by unsatisfactory electrical performance, thick semiconductor layers, and low device density. Herein, a facile and scalable 2D semiconductor printing strategy is demonstrated utilizing the interface capture effect and hyperdispersed 2D nanosheet ink to fabricate high‐quality and atomic‐thick semiconductor thin‐film arrays without additional surfactants. Printed robust thin‐film transistors using 2D semiconductors (e.g., MoS2 ) and 2D conductive electrodes (e.g., graphene) exhibit high electrical performance, including a carrier mobility of up to 6.7 cm 2 V −1 s −1 and an on/off ratio of 2 × 10 6 at 25 °C. As a proof of concept, 2D transistors are printed with a density of ≈47 000 devices per square centimeter. In addition, this method can be applied to many other 2D materials, such as NbSe2, Bi2 Se3, and black phosphorus, for printing diverse high‐quality thin films. Thus, the strategy of printable 2D thin‐film transistors provides a scalable pathway for the facile manufacturing of high‐performance electronics at an affordable cost. Abstract : A facile and scalable 2D semiconductor printing strategy utilizing the interface capture effect and hyperdispersed 2D nanosheet ink to print arrays of atomic‐thick semiconducting thin films is demonstrated, which enables printed devices with micrometer‐scale resolution, high density, and attractive performance, thus paving the way for practical large‐area application of 2D crystals in electronic devices at an affordable cost.